Does Inner Awareness Always Accompany Outer Awareness During Perception? - Chaturvedi, Madhu Mangal; Ravishankar Sarma, A. V. (Problemos, 2019)
In the present paper, we defend the thesis that outer-world-directed perceptual consciousness is always accompanied by an inner awareness (IAOA). This is contrary to the view that outer-world-directed conscious mental states are not accompanied by an inner awareness, which is held by Gennaro (2008) against Kriegel’s (2009a and 2009b) self-representationalism. We attempt to show why philosophers like Gennaro get it wrong when they deny the IAOA thesis by critically examining his arguments against it and by giving arguments in its favour.